The mechanism of ferroptosis in early brain injury after subarachnoid hemorrhage - Deng, Xinpeng; Wu, Yiwen; Hu, Ziliang; Wang, Shiyi; Zhou, Shengjun; Zhou, Chenhui; Gao, Xiang; Huang, Yi (Frontiers in Immunology, 2023)
Subarachnoid hemorrhage (SAH) is a cerebrovascular accident with an acute onset, severe disease characteristics, and poor prognosis. Within 72 hours after the occurrence of SAH, a sequence of pathological changes occur in the body including blood-brain barrier breakdown, cerebral edema, and reduced cerebrovascular flow that are defined as early brain injury (EBI), and it has been demonstrated that EBI exhibits an obvious correlation with poor prognosis. Ferroptosis is a novel programmed cell death mode. Ferroptosis is induced by the iron-dependent accumulation of lipid peroxides and reactive oxygen species (ROS). Ferroptosis involves abnormal iron metabolism, glutathione depletion, and lipid peroxidation. Recent study revealed that ferroptosis is involved in EBI and is significantly correlated with poor prognosis. With the gradual realization of the importance of ferroptosis, an increasing number of studies have been conducted to examine this process. This review summarizes the latest work in this field and tracks current research progress. We focused on iron metabolism, lipid metabolism, reduction systems centered on the GSH/GPX4 system, other newly discovered GSH/GPX4-independent antioxidant systems, and their related targets in the context of early brain injury. Additionally, we examined certain ferroptosis regulatory mechanisms that have been studied in other fields but not in SAH. A link between death and oxidative stress has been described. Additionally, we highlight the future research direction of ferroptosis in EBI of SAH, and this provides new ideas for follow-up research.